2021
DOI: 10.3390/ijerph18136719
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Promotion of Cannabidiol (CBD) Products in Online Vape Shops

Abstract: Vaping products containing cannabidiol (CBD), a cannabis-derived compound used in wellness products and available in all 50 US states, were recently implicated in outbreaks of poisonings. Little is known about the commercial availability of CBD products in vape shops (i.e., stores that sell e-cigarettes). To document the availability and marketing of CBD products in online vape shops, in June 2020, we used the Google Chrome browser without cached data to collect the first two pages of search results generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Consistent with previous studies [ 34 , 42 , 43 ], merchants indicated that CBD and related paraphernalia is prominent within the vape retail setting, with 73.3% selling CBD vape products and 80.0% selling other CBD products. Moreover, participants reported that CBD would continue to be an important component of their product offerings, likely reflecting the rapid expansion of the CBD market (including products administered similarly to tobacco products, e.g., vaped or smoked) [ 57 , 58 , 59 ]. Roughly one-tenth of our sample reported selling vape products containing THC, and about one-sixth intended to sell delta-8-THC and/or kratom products in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [ 34 , 42 , 43 ], merchants indicated that CBD and related paraphernalia is prominent within the vape retail setting, with 73.3% selling CBD vape products and 80.0% selling other CBD products. Moreover, participants reported that CBD would continue to be an important component of their product offerings, likely reflecting the rapid expansion of the CBD market (including products administered similarly to tobacco products, e.g., vaped or smoked) [ 57 , 58 , 59 ]. Roughly one-tenth of our sample reported selling vape products containing THC, and about one-sixth intended to sell delta-8-THC and/or kratom products in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic use was frequently reported in a self-selected convenience sample of CBD users mainly from the US [ 16 ], and in a Swiss study [ 33 ]. Nevertheless, we cannot draw definitive conclusions about CBD’s impact on various health conditions—including anxiety, sleeping disorders and chronic pain [ 8 ]—which are often cited as reasons for its use [ 6 , 16 , 17 , 18 , 34 ], and which are often described as beneficial on internet sites, often for marketing purposes [ 35 , 36 ]. The frequency of CBD use did not differ between clusters (daily use between 10 and 28%).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin ENNDS were promoted as a smoking cessation aid in Korea in 2016123 and were described on the US market in 2018 34. CBD products were commonly found in US online vape shops in 2021 124…”
Section: Tobacco and Cannabis Product Convergencementioning
confidence: 99%